2013
DOI: 10.1182/blood-2012-08-447599
|View full text |Cite
|
Sign up to set email alerts
|

SPIB, a novel immunohistochemical marker for human blastic plasmacytoid dendritic cell neoplasms: characterization of its expression in major hematolymphoid neoplasms

Abstract: Key Points• SPIB is an Ets transcription factor involved in plasmacytoid dendritic cell differentiation.• SPIB protein expression can be used as a marker for human blastic plasmacytoid dendritic cell neoplasms.SPIB is an Ets transcription factor that is expressed exclusively in mature B cells, T-cell progenitors, and plasmacytoid dendritic cells. In the present study, we developed a novel mAb against the SPIB protein and characterized its expression in major hematolymphoid neoplasms, including a series of 45 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…Remarkably, the high level of performance of the clone 124B3.13 is unique among the large set of PDC markers commonly used for BPDCN diagnosis, such as CD123, TCL1, BCL11a, CD2AP, as well as SPIB. [1][2][3]9 Moreover, our findings complement previously published data obtained by flow cytometry using the AC144 clone, 10 that demonstrated that positivity for BDCA-2 has the highest diagnostic score within a panel of markers used for BPDCN identification and confirmed that BPDCN does not cross the boundary with other hematopoietic neoplasms.…”
supporting
confidence: 80%
“…Remarkably, the high level of performance of the clone 124B3.13 is unique among the large set of PDC markers commonly used for BPDCN diagnosis, such as CD123, TCL1, BCL11a, CD2AP, as well as SPIB. [1][2][3]9 Moreover, our findings complement previously published data obtained by flow cytometry using the AC144 clone, 10 that demonstrated that positivity for BDCA-2 has the highest diagnostic score within a panel of markers used for BPDCN identification and confirmed that BPDCN does not cross the boundary with other hematopoietic neoplasms.…”
supporting
confidence: 80%
“…Furthermore, Spib −/− pDCs exhibit attenuated expression of pDC-specific genes and display defects in type I IFN production following TLR7 or TLR9 stimulation. SPIB was also recently shown to be a novel immunohistochemical marker for the identification of human blastic pDC neoplasms 56 .…”
Section: Development Of Pdcsmentioning
confidence: 99%
“…Interpersonal and intrapersonal immunophenotypic variations, such as CD4/CD56 positivity followed by negativity for both markers in subsequent biopsy specimens from a single patient, have been reported. 5,7 These findings underscore the importance of adding new antigens to the known repertoire of proteins expressed by BPDCN because their assessment may aid in early recognition of this tumor or help explain its biology.…”
Section: Discussionmentioning
confidence: 95%
“…1-6 However, this profile overlaps substantially with those of other hematolymphoid malignant neoplasms, predominantly NK cell lymphoma and/or leukemia and myeloid leukemias with skin involvement. 2,4-7 Moreover, the immunophenotypic diversity of BPDCN is greater than previously recognized. 2,5,7 Although the exact proportion of aberrant phenotypes remains unknown, negativity of at least 1 of the 4 markers CD4, CD56, CD123, and TCL-1 was demonstrated in 34% to 36% of cases in 2 large studies, emphasizing the need to disclose additional immunophenotypic features of this lethal neoplasm.…”
mentioning
confidence: 93%
See 1 more Smart Citation